BLOCKING ACCESS POLICY OF UNREGISTERED PRIVATE ELECTRONIC SYSTEM OPERATORS IN HUMAN RIGHTS PERSPECTIVE - Rinalvin Achmad Wiryawan; Istislam; Dhia Al Uyun (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The decision of the Panel of Judges in the State Administrative Court Decision at the Jakarta State Administrative Court Number 424/G/TF/2022/PTUN.JKT, contradicts with many human rights law, especially related to the right to communicate and obtain information and economic rights. The right to communicate and to access and obtain information is a right guaranteed and recognized by the Indonesian Constitution as stipulated in Article 28F of the 1945 Constitution, and regulated in Articles 14 of the Human Rights Act. In addition, the right to communicate and obtain information is also regulated internationally in the provisions of Article 19 of the Universal Declaration of Human Rights, and Article 19 of the International Covenant on Civil and Political Rights (ICCPR) which has been ratified in the provisions of the Law Number 12 of 2005 concerning the Ratification of the ICCPR (KIHSP Law). The right to economy and employment is a human right guaranteed in the Indonesian constitution, as stipulated in Article Article 27 paragraph (2) UUD NRI Tahun 1945, and regulated internationally in the provisions of Article 1 Number 2, Article 5 paragraph (2), and Article 6 of International Covenant on Economic, Social, and Cultural Rights (ICESCR) that has been ratified in the provisions of Law Number 11 of 2005 concerning the Ratification of the International Covenant on Economic, Social, and Cultural Rights (KIHESB Law).